No good deals - no bad models - Nina Boyarchenko; Mario Cerrato; John Crosby; Stewart Hodges (Federal Reserve Bank of New York, 2012)
Faced with the problem of pricing complex contingent claims, investors seek to make their valuations robust to model uncertainty. We construct a notion of a modeluncertainty-induced utility function and show that model uncertainty increases investors' effective risk aversion. Using this utility function, we extend the no good deals methodology of Cochrane and Saá-Requejo (2000) to compute lower and upper gooddeal bounds in the presence of model uncertainty. We illustrate the methodology using some numerical examples.
Keywords: G12; G13; 330; asset pricing theory; good-deal bounds; Knightian uncertainty; model uncertainty; contingent claim pricing; model-uncertainty-induced utility function